Budidaya Sapi Perah Melalui Aplikasi Teknologi Fermentasi Hijauan Pada Kelompok Peternak Andini Lestari - Syamsi, Afduha Nurus; Harwanto, Harwanto (Kreativasi : Journal of Community Empowerment, 2023)
The Andini Lestari Dairy Farmers Group (ALDFG) runs traditional dairy farming. Farmer members are not able to store forage when conditions are in excess nor are they able to provide good forage substitutes during shortages. The aim of this activity is to apply feed fermentation technology in the ALDFG to increase livestock productivity through the feed. The target activity are 17 farmers. The method was socialization, counseling, making demonstration plots, and evaluation. All the results of the activities are discussed descriptively. The results of the activity showed that the demonstration plot for making fermented feed was successfully carried out with the output of fresh grass silage and fermented rice straw. The quality of livestock milks also improved after the application of fermented feed as supplementation of 40% forage in the ration. The survey results showed that 64.71% of farmers were interested, 23.53% said they were not interested, and 11.76% said they were hesitant to apply the fermented feed technology that had been given in the extension, there are 3 (17.65%) farmers who still consistently apply fermented feed. This activity concludes that the application of forage fermentation technology in ALDFG can improve the quality of milk and increase the interest 17.65% of the farmer to consistently apply the technology.